2015
DOI: 10.3389/fpls.2014.00787
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and physiological responses of potato (Solanum tuberosum L.) plantlets to gradient saline stress

Abstract: Salinity is one of the major abiotic stresses that impacts plant growth and reduces the productivity of field crops. Compared to field plants, test tube plantlets offer a direct and fast approach to investigate the mechanism of salt tolerance. Here we examined the ultrastructural and physiological responses of potato (Solanum tuberosum L. c.v. “Longshu No. 3”) plantlets to gradient saline stress (0, 25, 50, 100, and 200 mM NaCl) with two consequent observations (2 and 6 weeks, respectively). The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
69
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 126 publications
(153 reference statements)
12
69
0
1
Order By: Relevance
“…Salinity causes an increase in root zone osmotic pressure, which ultimately results in cell dehydration and accumulation of higher amount of Na + and Cl -ions in soil solution that disturbs the availability of the nutrient especially K + (Hasanuzzaman et al, 2013;Farooq et al, 2015). Progressive built up of Na + and Cl -leads to nutrient starvation in seeds through ionic imbalance that restricts the embryo to absorb water and inhibits radicle growth and delays emergence (Gupta et al, 1993;Gao et al, 2014). It is obvious from current study that salt stress adversely affected emergence potential of cucumber genotypes but seed priming considerably mitigated the drastic effects of salinity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity causes an increase in root zone osmotic pressure, which ultimately results in cell dehydration and accumulation of higher amount of Na + and Cl -ions in soil solution that disturbs the availability of the nutrient especially K + (Hasanuzzaman et al, 2013;Farooq et al, 2015). Progressive built up of Na + and Cl -leads to nutrient starvation in seeds through ionic imbalance that restricts the embryo to absorb water and inhibits radicle growth and delays emergence (Gupta et al, 1993;Gao et al, 2014). It is obvious from current study that salt stress adversely affected emergence potential of cucumber genotypes but seed priming considerably mitigated the drastic effects of salinity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Such hyper-osmotic disturbance and hyper ionic toxic lead to hang-up seed germination and growth of seedlings (Hasegawa et al, 2000). Salt stress causes cell dehydration due to accumulation of Na + and Cl -ions in soil (Gupta et al, 1993) which decreases the availability of K + ions, such conditions restricted the seeds to absorb water for embryo expansion; consequently inactivation of enzymes, nutrient starvation, ionic toxicity and oxidative stress in tissues (Gao et al, 2014). Moreover, excessive salt ions disintegrate radicle and plumule tissues and inhibited radicle growth, which delayed emergence of seedlings (Shahid et al, 2011;El Harfi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Increased leaf succulence might have resulted from the increase in water uptake and turgor pressure as a result of cells having a higher solute concentration (Jennings, 1976). It is worthy to et al (2010) on Ziziphus spina-christi and Gao et al (2014) on potato plantlets. The number of leaves found to be decreased to progressing salinity levels (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Decrease of SOD and GPX activities under NaCl stress was recorded which can be explained as an inhibition of nitrogen uptake which then upregulate peptide biosynthesis of GPX and SOD antioxidant enzyme via inhibition of the genes encoding enzymes (Khodary, 2004). Gao et al (2015) showed that the activities of SOD in leaves of potato plantlets significantly increased with the increase of NaCl concentration (0∼100 mM) in medium. When exposed to 200 mM NaCl, especially after 6 weeks, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Bruns and HechtBuchholz (1990) found that the salt-induced changes were mainly observed in the chloroplasts, especially in the thylakoids. Although the ultrastructural alterations induced by saline have been reported in many plant cells, but information regarding the effects of salinity on potato cells cultured in vitro is not specified and is incomplete (Gao et al, 2015). The trait measured under the current study were increased when treated with the SiO 2 -NPs under the lower concentration of SiO 2 -NPs (50 mg L ) and also the addition of SiO 2 -NPs at 50 mg L -1 in combination with 50 mM NaCl or 100 mM NaCl triggered a significant beneficial impact to salinity treatment on some plant growth traits.…”
Section: Discussionmentioning
confidence: 99%